PTU-132 Normal alt – missed opportunities to find fibrosis. lessons from ILFT. (8th June 2018) - Robinson, Emma; Miller, Michael H; Brennan, Paul; Dillon, John F; Dow, Ellie; Bartlett, Bill; Donnan, Peter; Boyd, Kathleen
Abstract : Introduction: Liver Function Tests (LFTs) are frequently checked in primary care although liver disease is not suspected in the majority of cases. Despite this up to 20% of LFTs are abnormal. A significant percentage are never investigated, raising the possibility of missing significant and potentially treatable liver disease at an earlier stage. The intelligent LFT pathway (iLFT) was designed to risk stratify patients with abnormal LFTs into three categories. 1 Serious or complex liver disease that requires secondary care 2. Less significant disease that could be managed in primary care 3. Diagnostic uncertainty requiring further investigation. Alanine transaminase in an important component of LFTs. Previous studies have suggested the accepted reference range is too high, leading to the possibility of missed diagnosis. Method iLFT uses the combination of diagnostic criteria for liver disease, an investigation ordering and reporting system (ICE), and the tracked blood sciences system (Siemens). iLFT produces an automated diagnosis or description of the abnormality with staging information and suggestions for further management including referral criterion which is sent to the GP. A step wedge design trial was conducted in 6 GP practices (covering 30 000 patients). Patients at the practices with LFTs requested in the preceding 6 months were retrospectively used as controls. GPs requested the iLFT option and those with abnormal LFTs were assessed. A sub study analysis was performed within the iLFT intervention arm, an alternative normal range for ALT (Male <30, Female <19) was implemented and outcomes compared to the conventional normal range (M and F<55) including a cost effectiveness analysis. Results: 229 patients were included in the study. Using the lower ALT range: the number of subjects with abnormal LFTs increased from 64 (27.9%) to 140 (61.1%). Mean age was 50.9 (SD 14.77), percentage male 42.9% (n=60), and average BMI 29.7 (SD 3.82). Of the 76 with ALT <55, 13 more patients were found to have liver fibrosis due to either alcohol related (ALD) or non-alcohol related fatty liver disease (NAFLD) and a further 10 patients had non fibrotic ALD or NAFLD. iLFT remained cost effective with the amended ALT ranges and showed an incremental care- equivalent ratio (ICER) of £137 as well as a lifetime increase in quality adjusted life years. Conclusion: Using a reduced ALT cut off in iLFT increases the rate of liver diagnosis enabling earlier intervention. It also remains cost effective compared to standard practice.